SAT0093 Quantification of Bone Marrow Edema by Using Magnetic Resonance Imaging for the Assessment of Neck Pain Only Marginally Reflects Clinical Evaluation in Patients with Rheumatoid Arthritis and Ankylosing Spondylitis. (23rd January 2014) - Baraliakos, X.; Heldmann, F.; Suppiah, R.; McQueen, F.; Braun, J.
Abstract : Background: Despite the differences in the pathogenesis of rheumatoid arthritis (RA) and ankylosing spondylitis (AS), neck pain is a frequent clinical symptom in both diseases that was recently shown to correlate with disease activity. Objectives: In this study, we evaluated the correlation between subjective reports of neck pain and objective signs of inflammation by quantification of bone marrow edema (BME) as detected by MRI in patients with RA and AS. Methods: MR images (STIR sequence) of the cervical spine together with clinical and laboratory data of 40 patients (34 RA, 6 AS) who had participated in the recently presented CASSANDRA trial were included. MRI were assessed by two readers who were blinded for clinical data using a recently published MRI scoring system, with quantification of the extension of BME in the atlantoaxial region, corpus, facet joints and processus spinosus of all cervical vertebrae, ranging from 0-57 points. In addition, presence or absence of degenerative changes was also recorded. Results: Baseline characteristics, neck pain and MRI scores did not differ between RA and AS patients. The mean age was 57.5±11.8 years, 33/40 patients (82.5%) were female, the mean symptom duration for neck pain was 10.6±8.8 years, cervical rotation 51.0±17.2 degrees, CRP 0.9±1.3 mg/dl, ESR 19.8±26.6 mm/1h, FFbH 58.1±26.3 and the Northwick Park score was 46.0±17.5. BME was detected in 24/40 patients (60%), 5 of which (20.8%) had atlantoaxial involvement, 18 had BME in the vertebral body (75%), 7 in the facet joints (29.2%) and 11 in the processus spinosus (45.8%). Degenerative changes were seen in 21/40 patients (52.5%). Of those 21 patients, all (100%) had also signs of BME in the corpus, while from the 19 patients without degenerative changes, only 3 patients (15.8%) had BME in the corpus. In the more detailed analysis of the total of 240 evaluated vertebral bodies, 27 (11.3%) vertebral bodies had degeneration and in parallel inflammation in the corpus, while 24 (10%) had only degeneration, 11 (4.6%) had only inflammation in the corpus, and 178 (74.2%) had neither lesion. There was no correlation between the amount or the extension of BME and clinical or laboratory parameters for neck pain or cervical spine mobility. However, a significant difference (p=0.038) was found for BME scores of patients with a pain intensity (0-10 NRS) of ≥ 5 (5.8±6.5 scoring points) vs. < 5 (1.9±25 scoring points). This was partly dependent on scores for the atlantoaxial region, although the mean number of scoring points did not differ. The correlation between readers was excellent (regression coefficient. 0.942). Conclusions: This study shows that the majority of patients with RA and AS had objective signs of BME but also degenerative changes as assessed by MRI at different locations in the cervical spine. Assessment of the the presence of BME in the atlantoaxial region is important in clinical practice, in addition to degenerative changes, since its presence seems to influence the intensity of neck pain reported by these patients. Disclosure of Interest: None Declared